The final curtain - Higashino, Keigo, 1958- (Higashino, Keigo, 1958- Kyoichiro Kaga mysteries, 2023)
"From the acclaimed author of Malice and Newcomer, a confounding murder in Tokyo is connected to the mystery of the disappearance and death of Detective Kaga's own mother. A decade ago, Tokyo Police Detective Kyoichiro Kaga went to collect the ashes of his recently deceased mother. Years before, she ran away from her husband and son without explanation or any further contact, only to die alone in an apartment far away, leaving her estranged son with many unanswered questions. Now in Tokyo, Michiko Oshitani is found dead many miles from home. Strangled to death, left in the bare apartment rented under a false name by a man who has disappeared without a trace. Oshitani lived far away in Sendai, with no known connection to Tokyo - and neither her family nor friends have any idea why she would have gone there. Hers is the second strangulation death in that approximate area of Tokyo - the other was a homeless man, killed and his body burned in a tent by the river. As the police search through Oshitani's past for any clue that might shed some light, one of the detectives reaches out to Detective Kaga for advice. As the case unfolds, an unexpected connective emerges between the murder (or murders) now and the long-ago case of Detective Kaga's missing mother. The Final Curtain, one of Keigo Higashino's most acclaimed mysteries, brings the story of Detective Kaga to a surprising conclusion in a series of rich, surprising twists"--